Considerações teóricas entre dois sistemas de frenagem para bancada de testes de protótipos de rotores eólicos de pequeno porte - Martins, Marcelo Albuquerque (2018)
This paper aimed to evaluate the applicability of two types of braking systems to a test bench of an educational laboratory for wind rotors, whose current braking system is a drum brake. The first system is an eddy current brake, where an electromagnet induces electric currents on an aluminum disc. The second system is based on the viscous effect and was designed as a brake formed by an aluminum disc parallel to a smooth surface where there is a thin layer of fluid therebetween, so that the braking torque is modified by changing the height in the layer of fluid. The analytical model developed by Wouterse (1991) was applied to describe the behavior of the electromagnetic brake, whereas the behavior of the brake by viscous effect was described by a model developed from Newton's Law for unidirectional flows. After this, prototypes of each of the brakes were tested, so that it would be possible to compare the experimental measurements with the analytical estimates. Thus, for the electromagnetic brake prototype, the measured braking torque values were, on average, 22.7% lower than the values estimated analytically. And for the viscous-effect brake prototype, the analytical torque estimates were 52.7% lower than the torque values measured on the test, on average. In addition, the minimum torque requirements to be achieved by the brake systems have been calculated so that these systems can be properly applied to the test bench for wind rotors. From this, it was possible to estimate that, if they were implemented to the test bench, the brakes by electromagnetic effect and by viscous effect would produce maximum torque 2.81 and 3.54 times higher than the minimum requirements, respectively.